The Role of Internet of Things in Smart Business Decision-Making: A Narrative Review - Liantifa, Melifia; Hendra; Sekianti, Atik (Novatio : Journal of Management Technology and Innovation, 2025)
The Internet of Things (IoT) has emerged as a critical driver of smart business decision-making, enabling organizations to enhance efficiency, transparency, and responsiveness across industries. This narrative review examines the integration of IoT into business systems, focusing on its contributions to Enterprise Resource Planning (ERP), marketing strategies, sustainability leadership, smart environments, and sector-specific applications in agriculture, education, and healthcare. Literature was systematically collected from Scopus, Web of Science, and Google Scholar, using targeted keywords and Boolean operators. Inclusion criteria prioritized peer-reviewed studies that examined IoT in relation to business decision-making, resulting in a dataset of empirical and conceptual research published between 2018 and 2024. Findings reveal that IoT enhances decision-making accuracy through ERP integration, strengthens marketing strategies by enabling real-time consumer insights, and supports sustainability leadership by advancing Environmental, Social, and Governance (ESG) practices. In addition, IoT facilitates the development of smart environments that leverage big data and artificial intelligence for predictive analytics. Sectoral evidence confirms IoT’s effectiveness in improving agricultural productivity, optimizing educational management, and enabling remote healthcare monitoring. Nonetheless, critical systemic challenges persist, particularly cybersecurity threats such as data breaches, lack of common interoperability standards across IoT platforms, and infrastructural readiness gaps in regions with limited digital capacity. These barriers highlight the need for supportive policies, investment in digital infrastructure, and organizational cultures receptive to technological change. Future research should focus on empirical validation of IoT’s impact on managerial decision quality and explore cross-sectoral comparisons to enrich theoretical and practical understanding. By addressing these challenges, IoT can fulfill its promise as a transformative enabler of sustainable and innovative business strategies.